Experimental Study on Producer Gas Generation from Acacia Wood Using a Cross-Draft Biomass Gasifier - Sookramoon, Krissadang (Engineering, Technology & Applied Science Research, 2025)
This study presented the development of a cross-draft biomass gasifier for electricity generation on a small scale using Acacia wood as fuel. The gasifier was constructed from two welded oil drums, with a fuel capacity of 20 kg and a combustion chamber volume of 0.444 m3. The producer gas was utilized to power a HONDA GX160 gasoline engine attached to an alternator. The apparatus achieved a maximum electrical power output of 31.94 W at a speed of 2,780 rpm and average power output of 26.73 W at 1,393.56 rpm. Temperature was taken in the major areas of operation, including drying, pyrolysis, combustion, and reduction using thermocouples, while the major components of the producer gas were identified to be carbon monoxide (CO), hydrogen (H2), and methane (CH4). The experimental results revealed that the electric power output of the Acacia wood gasification system which ranged from 27.68 to 31.94 W was comparable to that of the conventional gasoline operation (29.48 W), which made it suitable for energy generation. Future work should focus on the enhancement of the gas quality and overall efficiency.